A roadmap to increasing access to AQP4-Ig testing for NMOSD: expert recommendations - Vassão-Araujo, Raquel; Apóstolos, Samira; Jansen, Angela Marie; Lana-Peixoto, Marco A.; Gomes Neto, Antonio Pereira; Rico-Restrepo, Mariana; Alves-Leon, Soniza Vieira; Sato, Douglas Kazutoshi (Arquivos de Neuro-Psiquiatria, 2025)
The discovery of aquaporin 4 immunoglobulin G (AQP4-IgG) autoantibody, present in ∼80% of patients with neuromyelitis optica spectrum disorder (NMOSD), dramatically improved its diagnosis, treatment, and prognosis. While Brazil has a higher prevalence of NMOSD (up to 4.5 per 100,000 people) compared with global averages, disparities in access to testing in Brazil impede early diagnosis and treatment. To tackle these issues, the Americas Health Foundation convened a three-day virtual conference with six Brazilian NMOSD experts. This paper emphasizes the importance of addressing the gaps in physicians' knowledge about NMOSD. Stakeholders, including government agencies, should develop national programs for continuing medical education. The public healthcare system should ensure the availability and accessibility of AQP4-IgG antibody testing. Clinical practice guidelines for NMOSD diagnosis and treatment must be established. Such guidelines will enable healthcare providers to manage patients promptly after the initial attack, reducing relapses and improving quality of life. Finally, addressing the fragmented healthcare system, including bridging the gap between public and private institutions and improving access to telemedicine, will aid individuals in Brazil with NMOSD in receiving early diagnosis and treatment. NMOSD presents unique challenges in Brazil because of its higher prevalence and limited access to crucial AQP4-IgG tests. Overcoming these challenges requires collaboration among experts, healthcare providers, government agencies, and the public healthcare system to improve diagnosis, treatment, and patient outcomes.
Keywords: Aquaporin 4; Autoantibodies Diagnostic Techniques and Procedures; Healthcare Disparities; Neuromyelitis Optica